Nemesis - Reichs, Brendan (Reichs, Brendan. Project nemesis, 2017)
As the Anvil, an enormous asteroid, threatens to end all life on Earth, sixteen-year-old Min begins to uncover a lifetime of lies and a sinister conspiracy involving all students in her sophomore class in Fire Lake, Idaho.